ANALISIS HUBUNGAN KEBERADAAN PT. SDIC PAPUA CEMENT INDONESIA TERHADAP SOSIAL EKONOMI MASYARAKAT DI MARUNI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Meylin Randongkir; Yulius G. Pangkung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
The importance of analysing the relationship between the existence of PT. SPCI and the socioeconomic condition of the Maruni village community is to determine how close the relationship between PT. SPCI and the Maruni village community. It turns out that after analysing the results it shows that there is a fairly positive relationship between the existence of PT. SPCI and the basic livelihoods of the community and employment. Meanwhile, there has no association between the presence of PT. SPCI and job opportunities among the villagers.